PENGENALAN LITERASI NUMERASI BERBASIS KEMARITIMAN DI TK NEGERI MAWASANGKA - Rasida, Rahima; Kurniati, Asma; Marwah, Marwah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe the process of introducing maritime-based literacy and numeracy to early childhood at Mawasangka State Kindergarten, located in the coastal area of ​​Central Buton Regency. This research approach uses a participatory qualitative method with data collection techniques in the form of observation, interviews, and documentation. Learning activities are focused on developing children's abilities in recognizing numbers, patterns, classifications, and stories, through maritime media and themes that are relevant to the surrounding environment, such as pictures of fish, ships, shells, and sea-themed stories. The results of the study showed that children showed high enthusiasm, active involvement, and increased understanding of the concept of numeracy and literacy contextually. In addition, this activity supports the achievement of seven aspects of early childhood development, especially in the cognitive, language, socio-emotional, and gross motor aspects. Maritime-based learning has been proven to be able to integrate local values ​​into the PAUD curriculum, as well as being an innovative approach to building basic numeracy literacy skills from an early age. These findings are recommended to be adopted by PAUD institutions in other coastal areas as a form of transformative and inclusive contextual education.